2016
DOI: 10.11144/javeriana.upsy15-4.vero
|View full text |Cite
|
Sign up to set email alerts
|

Validación de la Environmental Reward Observation Scale (EROS) en población Colombiana

Abstract: RESUMENSe estimaron las propiedades psicométricas de la Environmental Reward Observation Scale (EROS) en población colombiana, con dos muestras: población comunitaria y clínica. Para la primera, se evaluaron 507 personas en 22 departamentos del país, con edades entre 18 y 72 años, 60.5 % mujeres y el restante hombres; la segunda muestra estuvo compuesta por 68 personas, con edades comprendidas entre 18 y 72 años, atendidas en el momento de la evaluación por profesionales en salud mental. Se realizó la aplicaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
1
0
4
Order By: Relevance
“…Regarding evidence of construct validity, the confirmatory factor analysis indicates the unidimensionallity of the scale. This result coincides with those reported by Armento and Hopko (2007) and by other validation studies (Barraca & Pérez-Álvarez, 2010;Valderrama-Díaz et al, 2016;Wagener & Blairy, 2015). It should be noted that, in our study, most of the fit indexes were observed to be below the standard criterion, and only the MIREAL and CFI indexes can be considered appropriate.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding evidence of construct validity, the confirmatory factor analysis indicates the unidimensionallity of the scale. This result coincides with those reported by Armento and Hopko (2007) and by other validation studies (Barraca & Pérez-Álvarez, 2010;Valderrama-Díaz et al, 2016;Wagener & Blairy, 2015). It should be noted that, in our study, most of the fit indexes were observed to be below the standard criterion, and only the MIREAL and CFI indexes can be considered appropriate.…”
Section: Discussionsupporting
confidence: 92%
“…In its original version, with a sample of American students, the scale showed a unifactorial structure with high internal consistency ( α = 0.85) and correlations, from moderate to strong, with different depression scales BDI-II = -0.78; CESD = -0.79; Zung Self-Rating Depression Scale = -0.54. In other validation studies which included the general population and also populations with emotional disorders, carried out with participants who were Spanish ( Barraca and Pérez-Álvarez, 2010 ), Colombian ( Valderrama-Díaz et al, 2016 ), or Belgian ( Wagener and Blairy, 2015 ), in all cases there were found to be appropriate levels of internal consistency and also significant signs of construct validity. Here the Spanish adaptation of the EROS was used ( Barraca and Pérez-Álvarez, 2010 ), for which data is available confirming its reliability ( α = 0.86) and validity (correlations with the BDI-II = -0.73; STAI-E = -0.80; STAI-R = -0.70; BADS-T = -0.69).…”
Section: Methodsmentioning
confidence: 97%
“…Se encuentra compuesta por 10 ítems con 5 opciones de respuesta de 0 a 4. En su confiabilidad presentó una buena consistencia interna (α = .87) (Valderrama-Díaz et al, 2016), y un test-retest de .84 (Armento & Hopko, 2007). Las evidencias de validez de la estructura interna mostraron que un factor explica 56.93% de la varianza total (Valderrama-Díaz et al, 2016).…”
Section: Formatos De Registro Del Manualunclassified
“…En Colombia se han desarrollado diferentes investigaciones afines a la AC: 1) evaluación de las propiedades psicométricas de escalas que evalúan el reforzamiento positivo contingente a la respuesta (índice de probabilidad de recompensa [RPI] [Reyes et al, 2023]; Escala de Observación de Recompensa del Ambiente [EROS] [Saavedra et al, 2023;Valderrama et al, 2016]) y factores de cambio propios de la AC (Escala de Activación Conductual para Depresión [BADS] [Leal-Hernández et al, 2023]); 2) estudios experimentales de caso único con el protocolo BATD con adolescentes (Guaidía, 2020), universitarios (Garcés et al, 2022;Gordillo, 2023), adultos con depresión (Pinzón-Corredor & Bianchi, 2023), personas con esclerosis lateral amiotrófica (Uribarren, 2020), entre otros, y 3) eficacia de protocolos BATD de única sesión con universitarios (Parra et al, 2019) y cuidadores (Cuevas, 2020).…”
Section: Introductionunclassified